Study on application of industrialized building system (IBS) in Perlis - Luqman Walid (School of Environmental Engineering, University Malaysia Perlis, 2012)
Industrialized Building Systems (IBS) is also known as the complete assembly construction. This system where components are manufactured at factories on or off site, transported and then assembled into a structure with minimum work. The main objective of this study is to find the implementation level and exposure of Industrialized Building Systems (IBS) method to population in Perlis. Perlis is a state that can be categorized as a small state and small size of population. Among methods implemented to aid this study were questionnaire, interview and secondary source information. From those methods, 70 % respondents know about this system in generally. While who know about this system more details and specifics were about 30 %. Eventually, more of respondents agree implementation this system at Perlis. Just are developers were disagree implementation this system in Perlis because the initial cost more higher. As conclusion, the application of this system in Perlis is suitable and developers must believe this system will give a better profit to them.